POSSIBLE NATURE OF THE SEISMIC BOUNDARY AT A DEPTH OF 70 KM - Levin B.W.; Rodkin M.V.; Sasorova E.V. (My University, 2007)
Classical works on seismology and the physics of the Earth distinguish a boundary at a depth of 70 km, which divides shallow-focus (shallow) and intermediate earthquakes that occupy the depth range from 70 to 300 km. It should be noted that shallow (<70 km) earthquakes comprise approximately 85% of the total number of recorded events. The nature of this boundary remains debatable so far.